Clinical characteristics of Chinese pediatric patients positive for anti-NMDAR and MOG antibodies: a case series - Kang, Qingyun; Kang, Hui; Liu, Shulei; Feng, Mei; Zhou, Zhen; Jiang, Zhi; Wu, Liwen (Frontiers in Neurology, 2024)
Introduction The cases of MOG-AD (MOG antibody-associated disorder) and anti-NMDAR encephalitis overlapping syndrome (MNOS) are rare, especially among pediatric patients, and their clinical understanding is limited. This study aimed to investigate the clinical manifestations, imaging findings, treatments, and prognosis of Chinese pediatric patients who tested positive for anti-NMDAR and MOG antibodies. Methods This retrospective study enrolled 10 MNOS pediatric patients, 50 MOG-AD (anti-NMDAR antibody-negative), and 81 anti-NMDAR encephalitis (MOG antibody-negative) pediatric patients who were admitted from July 2016 to June 2022 and used their clinical data for comparison. Results The MNOS patients had a significantly lower incidence of psycho-behavioral abnormalities and involuntary movements than anti-NMDAR antibody (+)/MOG antibody (−) patients and had a significantly higher incidence of sleep disorders, seizures, and psycho-behavioral abnormalities than MOG antibody (+)/anti-NMDAR antibody (−) patients. The MNOS patients had a significantly higher incidence of MRI abnormalities than the anti-NMDAR antibody (+)/MOG antibody (−) patients, while there was no significant difference in the incidence between the MNOS patients and the MOG antibody (+)/anti-NMDAR antibody (−) patients. No significant difference was seen in the initial mRS score between the three groups of patients. The anti-NMDAR antibody (+)/MOG antibody (−) patients had a higher rate of admission to the ICU, a longer length of in-hospital stay, and a higher rate of introduction to second-line treatment than the other two groups of patients. No significant difference was seen in the mRS score at the last follow-up and in the disease recurrence rate between the three groups. All these patients respond well to immunosuppressive therapy. Discussion In the presence of psycho-behavioral abnormalities, sleep disorders, and frequent seizures in MOG-AD patients or demyelinating symptoms of the central nervous system or demyelinating lesions on head MRI in anti-NMDAR encephalitis patients, the coexistence of MOG and anti-NMDAR antibodies should be considered and would suggest a diagnosis of MNOS for these patients. Immunotherapy is effective among these patients and should be given possibly earlier.